Broadband and high‐K passive balun using 16 sides geometry for silicon‐based RFICs. Issue 4 (1st February 2014) - Zhang, Hua Bin; Cai, Min; He, Xiaoyong; Wu, Haijun; Li, Zhengpin; Tang, F.
Abstract : A broadband and high‐ K monolithic passive balun for silicon‐based radio frequency integrated circuits (RFICs) are presented. It utilises the top level thick Cu metal and adopts a 16‐side geometry. The proposed balun is designed and fabricated with a 0.13‐μm CMOS mixed‐signal 1P6M process. The measured results show that the amplitude imbalance is < 0.2 dB and the phase imbalance is within 4° from the frequency range of 0.1–7 GHz. Compared with the typical octagonal balun, the proposed design achieves the same coupling coefficients K and attains an enhancement in the transmission efficiency S 21 within the frequency range of 0.1–20 GHz, and the consumed chip area is reduced by 3%.